Enriching the cognitive performance of mind for creative thinking in creative industries - Ab. Aziz Shuaib; Olalere, Folasayo Enoch (2014)
Highly creative thinkers have one thing in common; they tap into a force beyond the confines of their minds, and draw from it infinite amounts of wisdom, inspiration and success. Achieving this involves not just cognitive process of acquiring and utilizing knowledge, but also applying the power of imagination. Imagination helps to shatter the boundaries of the known and enters the domains of the unknown. Thus, to be a creative thinker, this brain-based skill must be fully active and utilized. Hence, this paper seeks to illuminate on how cognitive skills of the mind can be enhance for maximum performance in creative industry. The paper also identifies the three internal components that make up a creative mind; and also analyzed human subconscious mind and the role it plays in creative thinking and problem solving.